Poligami; antara Tuntunan Syara’ dan Problem Sosia: Studi Kasus dalam Rumah Tangga di Kota Palopo - Zulyadain, Zulyadain (Tasamuh: Jurnal Studi Islam, 2019)
In Islam, polygamy is allowed in based on QS. Al-Nisa, verse 3. However, in the same sura, which is in paragraph 129, stated that " And you will never be able to be equal [in feeling] between wives, even if you should strive [to do so]" in QS. Al-Nisa, verse 129, Allah swt gave a warning that the husband will not be able to do justice to their wives, which is a prerequisite for fair treatment of polygamy. Basically, polygamy can not be banned in general, for both Islamic law and positive law in Indonesia allows polygamy with strong reasons, there is permission from his wife, unable to do justice to the wives. And within reason and certain conditions must obtain permission from the court. This article will be discribe about polygamy in Palopo city.